2008
DOI: 10.1016/j.otohns.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Choanal atresia: Long‐term follow‐up with objective evaluation of nasal airway and olfaction

Abstract: Using the UPSIT, the bilateral CA patients have shown, on average, a moderate loss of the sense of smell when compared with normal controls of a similar age group. Acoustic rhinometry is not a useful study for posterior nasal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Congenital choanal atresia (CA) is an uncommon craniofacial anomaly characterized by obliterated posterior choanae leading to upper airway obstruction [3] [7] [8] [9]. It may be unilateral or bilateral [6] [7] [8] [9]. The exact embryologic explanation of CA is unclear until now.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital choanal atresia (CA) is an uncommon craniofacial anomaly characterized by obliterated posterior choanae leading to upper airway obstruction [3] [7] [8] [9]. It may be unilateral or bilateral [6] [7] [8] [9]. The exact embryologic explanation of CA is unclear until now.…”
Section: Discussionmentioning
confidence: 99%
“…In this pilot study, we present 3 cases of unilateral choanal atresia with significantly lower odor threshold postsurgically. To date, there are only 2 published studies focusing on the postsurgical olfactory performance of adults with choanal atresia [11, 12]. Both of them have reported that patients with unilateral atresia have normal olfactory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, olfactory evaluation has not been extensive in any of these studies. Gross-Isseroff et al [11] have tested their subject only in terms of odor threshold separately for each nostril, while Leclerc et al [12] have tested their 2 subjects with an odor identification test (both nostrils at once). Based on our findings, we suggest that olfactory testing of these patients should focus on all aspects of olfaction (identification, threshold, and discrimination) and should be performed separately for each nostril.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation